2014
DOI: 10.1111/jpc.12781
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of daily versus stoss vitamin D therapy in Aboriginal children

Abstract: Vitamin D insufficiency is common in Aboriginal children of Western Australia and stoss therapy is a safe alternative to daily vitamin D therapy but requires further evaluation of timing and doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…High-dose oral vitamin D has been shown to be safe and effective at rapidly increasing serum 25-OHD levels in vitamin D deficiency (23,30,31). Stoss therapy has been used successfully in children with cystic fibrosis (25), chronic kidney disease (26) and prior to hematopoietic stem cell transplant (27).…”
Section: Discussionmentioning
confidence: 99%
“…High-dose oral vitamin D has been shown to be safe and effective at rapidly increasing serum 25-OHD levels in vitamin D deficiency (23,30,31). Stoss therapy has been used successfully in children with cystic fibrosis (25), chronic kidney disease (26) and prior to hematopoietic stem cell transplant (27).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the trials in children have used single high doses of vitamin D [ 35 , 36 , 37 , 38 , 39 , 40 ] or compared different doses or duration of depot preparations [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] for treatment. There are only limited numbers of trials comparing low dose daily against intermittent depot vitamin D therapy [ 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. Studies using depot vitamin D treatment in children suggest that high-dose repletion approaches are safe and effective.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were treated with a single dose of cholecalciferol, according to hospital guidelines. Studies comparing single one-off with maintenance vitamin D therapy have shown it to be safe and effective ( 30 , 31 ), even up to 12 months after administration ( 32 ). However, randomised controlled trials provide some evidence to support the value of vitamin D maintenance therapy, rather than single doses, in paediatric asthma patients to prevent exacerbations ( 33 ).…”
Section: Discussionmentioning
confidence: 99%